PENGARUH CGPI, KUALITAS AUDIT, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PRAKTIK MANAJEMEN LABA: Studi Empiris Pada Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia - Anida Ikhwatun Karimah; Erma Setiawati (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the influence of CGPI, Audit Quality, Company Size, and Leverage on profit management in property and real estate companies listed on the Indonesia Stock Exchange. This study uses the disrectionary accrual method as a proxy to calculate profit management. The type of data used is secondary data. The data analysis technique in this study uses multiple linear regression analysis with data calculation using IBM SPSS Statistics 25 software. The sample of this study is 186 property and real estate companies listed on the Indonesia Stock Exchange in the period of 2019 - 2022 using the purposive sampling method. The results of the study show that 1) CGPI has no effect on profit management, 2) Audit quality has no effect on profit management, 3) Company size has no effect on profit management, 4) Leverage has no effect on profit management